Level of agreement between medical record and ICD-10-AM coding of mental health, alcohol and drug conditions in trauma patients. Issue 3 (September 2019) - Nguyen, Tu Q; Simpson, Pamela M; Braaf, Sandra C; Cameron, Peter A; Judson, Rodney; Gabbe, Belinda J
Background: Despite the reliance on administrative data in epidemiological studies, there is little information on the completeness of co-morbidities in administrative data coded from medical records. Objective: The aim of this study was to quantify the agreement between the International Classification of Diseases, Tenth Revision, Australian Modification (ICD-10-AM) administrative coding of mental health, drug and alcohol co-morbidities and medical records in a severely injured patient population. Method: A random sample of patients ( n = 500) captured by the Victorian State Trauma Registry and definitively managed at the state's adult major trauma services was selected for the study. Retrospective medical record review was conducted to collect data about documented co-morbidities. The agreement between ICD-10-AM data generated from routine hospital coding and medical record–based co-morbidities was determined using Cohen's κ and prevalence-adjusted bias-adjusted kappa (PABAK) statistics. Results: The percentage of agreement between the medical record and ICD-10-AM coding for mental health, drug and alcohol co-morbidities was 72.8%, and the PABAK showed moderate agreement (PABAK = 0.46; 95% confidence interval (CI): 0.37, 0.54). There was no difference in agreement between unintentional injury patients (PABAK = 0.52; 95% CI: 0.42, 0.62) compared with intentional injury patients (PABAK = 0.36, 95% CI: 0.23, 0.49), and no change in agreement for patients admitted before (PABAK = 0.40; 95% CI: 0.30, 0.50) and after the introduction of mandatory co-morbidity coding (PABAK = 0.46; 95% CI: 0.37, 0.54). Conclusion: Despite documentation in the medical record, a large proportion of mental health, drug and alcohol conditions were not coded in ICD-10-AM. Acknowledgement of these limitations is needed when using ICD-10-AM coded co-morbidities in research studies and health policy development. Implications: This work has implications for researchers of drug and alcohol abuse; mental health; accidents and injuries; workers' compensation; health workforce; health services; and policy decisions for healthcare, emergency services, insurance industry, national productivity and welfare costings reliant on those research outcomes.